Investigation of the Validity and Reliability of the Young Positive Schema Questionnaire on Turkish Adolescents - Yildirim, Musa; Yuksel Sahin, Fulya (SPRINGER, 2026)
Schema Therapy aims to regulate dysfunctional schemas that develop early in life and persist into adulthood. This approach incorporates a range of theoretical frame-works, including cognitive behavioral therapy, psychodynamic therapy, attachment theory, and gestalt therapy. This study aims to examine the psychometric properties of the Young Positive Schema Questionnaire (YPSQ) in an adolescent sample. The YPSQ was developed by Louis et al. (Psychol Assess 30(9):1199, 2018) and sub-sequently adapted to a Turkish adult sample by Veliba & scedil;o & gbreve;lu (2021). The sample of the present study comprised 777 adolescents enrolled in high school. Confirmatory factor analysis (CFA) was performed to assess the factor structure of the scale and the 14-factor structure was confirmed with 55 items (chi 2/df = 1.90, RMSEA = 0.03, CFI = 0.97, NFI = 0.96, GFI = 0.98, AGFI = 0.97). Item 53 in the original scale was eliminated due to a factor loading below 0.30. The factor loadings of the scale items range between 0.43 and 0.82. The criterion-related validity of the scale was assessed by examining the relationship between the Young Positive Schema Questionnaire and the Flourishing Scale. As a result, a high level of correlation was identified be-tween positive schemas and psychological well-being (r = .73, p < .01). The internal consistency of the sub-factors of the scale was assessed by examining the mean inter-item correlations, which ranged from 0.25 to 0.51. Consequently, the 14-factor structure of the scale was found to be compatible with both the original scale and the theoretical framework. The scale demonstrated adequate internal consistency. The correlation of the Young Positive Schema Questionnaire and its sub-dimensions with psychological well-being indicates satisfactory criterion-related validity.
Keywords: Schema therapy; Positive schemas; Validity; Reliability; SELF-COMPASSION; PERSONALITY; EMPATHY; ESTEEM; ALPHA; CHILD; Psychology